2021
DOI: 10.1108/jhr-01-2021-0008
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing caregivers' uncertainty of children undergoing cardiac surgery in Bangkok, Thailand

Abstract: PurposeThis study aims to determine the factors influencing caregivers' uncertainty about children undergoing cardiac surgery in a tertiary hospital in Bangkok, Thailand.Design/methodology/approachA correlational predictive study was conducted among 75 caregivers of children from infancy to fifteen years old who were undergoing first time cardiac surgery in a tertiary hospital in Bangkok, Thailand. Four questionnaires were inquired to evaluate caregivers' uncertainty about the illness, and influential factors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
(37 reference statements)
1
0
0
Order By: Relevance
“…Regarding to children gender, this study results showed that less than two third of them were boys. This finding was in line with [17] who studied "Factors influencing caregivers' uncertainty of children undergoing cardiac surgery in Bangkok, Thailand" and reported that 58.6% of the studied children were males. However, this study disagreed with [4] who studied " Role of tracheostomy in pediatric patients who underwent heart surgery: a single-center experience " and reported that 50.8% of them were female.…”
Section: Discussionsupporting
confidence: 88%
“…Regarding to children gender, this study results showed that less than two third of them were boys. This finding was in line with [17] who studied "Factors influencing caregivers' uncertainty of children undergoing cardiac surgery in Bangkok, Thailand" and reported that 58.6% of the studied children were males. However, this study disagreed with [4] who studied " Role of tracheostomy in pediatric patients who underwent heart surgery: a single-center experience " and reported that 50.8% of them were female.…”
Section: Discussionsupporting
confidence: 88%
“…We adjusted for confounding factors that may influence the level of parental uncertainty or anxiety [20,21]. These confounding factors included parental age, sex, and education (high: equal or higher than university level; low: equal or lower than junior college level); family income (high: family income more than USD 30,000 per year; low: family income equal or less than USD 30,000 per year); place of residence (urban or rural); presence of siblings; and children's age, sex, and heart disease type (PDA, ASD, or VSD).…”
Section: Confounding Factorsmentioning
confidence: 99%